2018
DOI: 10.1088/1741-4326/aadb48
|View full text |Cite
|
Sign up to set email alerts
|

A multi-scale model for stresses, strains and swelling of reactor components under irradiation

Abstract: Predicting strains, stresses and swelling in nuclear power plant components exposed to irradiation directly from the observed or computed defect and dislocation microstructure is a fundamental problem of fusion power plant design that has so far eluded a practical solution. We develop a model, free from parameters not accessible to direct evaluation or observation, that is able to provide estimates for irradiation-induced stresses and strains on a macroscopic scale, using information about the distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 67 publications
(172 reference statements)
4
70
0
Order By: Relevance
“…V 0 ij = −∂H int el /∂σ ij and Ω ijkl = −∂ 2 H int el /(∂σ ij ∂σ kl ) are two tensors, of second and fourth rank, respectively, that determine the change of the energy landscape due to the applied stress and to the interaction between the applied stress and the internal stress associated with the defect, respectively. The polarization tensor Ω ijkl can be defined as the difference of curvature in the free energy landscape basin because of the interaction of the stress fields, which stands for the difference of the compliance tensor in the vicinity of the defect [39,40].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…V 0 ij = −∂H int el /∂σ ij and Ω ijkl = −∂ 2 H int el /(∂σ ij ∂σ kl ) are two tensors, of second and fourth rank, respectively, that determine the change of the energy landscape due to the applied stress and to the interaction between the applied stress and the internal stress associated with the defect, respectively. The polarization tensor Ω ijkl can be defined as the difference of curvature in the free energy landscape basin because of the interaction of the stress fields, which stands for the difference of the compliance tensor in the vicinity of the defect [39,40].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Recently we have shown that it is possible to compute stresses and strains in reactor components on the macroscopic scale of centimetres and metres from the distribution of irradiation-induced defects [13]. As a source term, this model requires the spatially varying density of relaxation volumes of defects, and so allows the direct simulation of volumetric radiation-induced swelling and the associated stresses from an atomistic or object-based model.…”
Section: Introductionmentioning
confidence: 99%
“…One outstanding issue, which this paper is intended to address, is to have good data for the relaxation volumes of lattice defects, as while accessible from simulation for years, reporting this information has been somewhat neglected in favour of establishing accurate values of formation energies and ground-state structures. For example, a comprehensive compilation of data on relaxation volumes of individual self-interstitial and vacancy point defects derived from DFT calculations has been reported only recently [18,13,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires the bulk elastic Lamé parameters λ and µ, which we compute at the beginning of the simulation using the empirical potential supplied. The centreof-position of an object is taken to be [57] R = n a=1 P a R a n a=1 P a…”
Section: Parameterization Of Kmc Simulationsmentioning
confidence: 99%